(3QSGdI aj CQSWGWGdjS bGd Cf CWhd CYeOI GdLHGd hCHYO HYO GdZjhe aj GdLh SfI YTQ GUWGRjGs - (3GdaVd Hf MGJe GdfjQjRj, CHh GdYHGS,J (B310 (3g` s
(3ChdgG (B:s
(3bGd GdaVd Hf MGJe GdJHQjRi bGd CQSWGWGdjS Cf CWhd CYeOI GdLHGd hCHYO HYO GdZjhe ai GdLh SfI YTQ GUWGRjG s
(3BNQgG (B:s
(3hJQ GdbWYI ef Nha GdOGFQI GdJi aUdgG GdNWGf GdTYGYjGf Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHY hYTQhfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B147 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B66s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs